The novel human platelet septin SEPT8 is an interaction partner of SEPT4 - Bläser, Susanne; Horn, Julia; Würmell, Paul; Bauer, Heike; Strümpell, Sandra; Nurden, Paquita; Pagenstecher, Axel; Busse, Anja; Wunderle, Daniela; Hainmann, Ina; Zieger, Barbara (Thrombosis and Haemostasis, 2004)
Septins are a family of GTP-binding proteins, which are essential for active membrane movement such as cytokinesis and vesicle trafficking. In non-dividing cells (such as platelets and neurons) septins are implicated in exocytosis. Platelets from a SEPT5 knockout mouse showed an altered serotonin secretion and platelet aggregation, suggesting that SEPT5 is involved in secretion in platelets. Septins form complexes consisting of multiple septin polypeptides. Using the yeast two-hybrid system we had demonstrated that SEPT5 partners with SEPT8.The aim of this study was to identify other interaction partners of the human platelet septin SEPT8. Using the yeast two-hybrid system with SEPT8 as bait protein we identified the human septin SEPT4 as an interaction partner of SEPT8. The interaction between SEPT4 and SEPT8 was confirmed by immunoprecipitation. Expression analysis revealed that SEPT4 is also expressed in human platelets. Thus, SEPT4 is the third described platelet septin besides SEPT5 and SEPT8.Transmission electron microscopy of platelets revealed that SEPT8 and SEPT4 are localized surrounding α-granules (as it had been shown for the septin SEPT5) suggesting that the three septins may be components of the septin complex in platelets and contribute in such a way to platelet biology. Activation of platelets by agonists resulted in the translocation of SEPT4 and SEPT8 to the platelet surface indicating a possible functional role of these proteins in platelet granular secretion.
Keywords: Septins; SEPT4; SEPT8; Platelets; GTP-binding proteins